Law Review Of Dispute Resolution In The Land Acquisition For Development For Public Interest In Tegal Regency - Vita Purnamiati; Gunarto Gunarto; Sufi Hamdani Kurniawan (Jurnal Akta, 2019)
The purpose of this study was to determine: 1) Implementation of land acquisition for the construction of highways in the public interest, Tegal Regency. 2) Settlement of disputes in the implementation of land acquisition for the construction of public interest. 3) Obstacles and solutions in the procurement of land for public purposes in Tegal regency.The approach method in this research is juridical empirical research that emphasizes the behavior of individuals or communities in connection with the law. The data used are primary and secondary data obtained through interviews and literature, whereas the method of analysis with descriptive analysis method and qualitative analysis.Results of the research results can be concluded: 1) Implementation of land acquisition for public purposes, starting from planning, location determination, the establishment of the land procurement committee, price assessment, deliberation, decision and compensation stage damnification; 2) Settlement of disputes of land acquisition in the public interest the construction of toll roads in Tegal regency can be done with the courts and lanes deliberation. Tegal society more choose the path of deliberation for reasons more cost effective. Settlement of disputes by consultation carried out continuously and intensely to achieve a fair deal. 3) Obstacles and solutions in the procurement of land for public purposes in Tegal their third-party intervention, the buying and selling of land free, the process of inheritance that has not been behind the name, the pricing of compensation is not appropriate and the knowledge society that is lacking in the field land and construction of public interest. The solution to this committee is to socialize and intense deliberations to happens a fair deal for both sides.Keywords: Land Dispute; Land Acquisition; Public Interest.